Transkulturowy potencjał współczesnego kina europejskiego. O roli filmu w edukacji międzykulturowej dorosłych - Konieczna, Ewelina (Adult Education Discourses, 2020)
The purpose of the reflections in the article is an attempt to find an answer to the question of whether and how films speaking about the topic of multiculturalism could serve intercultural adult communication and education. The modern European cinema audience experiences multiculturalism and is encouraged to reflect on mutual acceptance and tolerance of cultural diversity. The representation in films of ethnical and racial minorities is connected with reflection on migratory movements and the issues of multicultural and transcultural societies. Transculturalism is characterised by cross cultural associations, fusions and convolution leading to the formulation of a novel cosmopolitan culture. Transculturalism acts as a unifying force of cultural diversity that not only brings together different cultures but also creates a new common culture